The Pengaruh Current Ratio, Receivable Turnover Ratio Dan Debt To Asset Ratio Terhadap Profitabilitas (Studi Pada Perusahaan Manufaktur Sektor Industri Barang Konsumsi Yang Terdaftar Di BEI Tahun 2015-2020) - Fachrun Nisa; Nunung Nurhasanah; Kosasih Kosasih (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
The purpose of this study was to determine the current ratio (CR), receivable turnover ratio (RTR) and debt to asset ratio (DAR) on profitability. Profitability is measured using net profit margin (NPM). The research conducted in this research is descriptive with a quantitative approach. The population in this study are manufacturing companies in the consumer goods industry sector listed on the Indonesia Stock Exchange (IDX) in 2015 – 2020. The sample of research data is 120. Based on the results of the study, that simultaneously CR, RTR, DAR affect NPM with a significant level of 0.008. Partially CR has a significant effect on NPM with a significant level of 0.048. Furthermore, RTR has a significant effect on NPM with a significant level of 0.003. And DAR has no effect on NPM with a significant level of 0.181. Keywords: CR, RTR, DAR, NPM